Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1289/ehp.1409529
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Heat-Related Mortality in an Elderly Urban Population by Vegetation (Urban Green) and Proximity to Water (Urban Blue): Evidence from Lisbon, Portugal

Abstract: Background:Urban populations are highly vulnerable to the adverse effects of heat, with heat-related mortality showing intra-urban variations that are likely due to differences in urban characteristics and socioeconomic status.Objectives:We investigated the influence of urban green and urban blue, that is, urban vegetation and water bodies, on heat-related excess mortality in the elderly > 65 years old in Lisbon, Portugal, between 1998 and 2008.Methods:We used remotely sensed data and geographic information to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(78 citation statements)
references
References 51 publications
(59 reference statements)
2
67
0
2
Order By: Relevance
“…Two studies sought to understand whether the relationship between heat and mortality was modified by greenness exposure and found that the association between temperature and mortality was attenuated in greener areas [54,55]. In Portugal, mortality was 14.7% (95% CI: 1.9, 17.5) higher comparing extremely hot days (> 99 th percentile of temperature) to other days in areas in the lowest greenness quartile (NDVI <0.23), but only 3.0% (95% CI: 2.0, 4.0) higher in areas in the highest NDVI quartile (>0.48) [55].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies sought to understand whether the relationship between heat and mortality was modified by greenness exposure and found that the association between temperature and mortality was attenuated in greener areas [54,55]. In Portugal, mortality was 14.7% (95% CI: 1.9, 17.5) higher comparing extremely hot days (> 99 th percentile of temperature) to other days in areas in the lowest greenness quartile (NDVI <0.23), but only 3.0% (95% CI: 2.0, 4.0) higher in areas in the highest NDVI quartile (>0.48) [55].…”
Section: Methodsmentioning
confidence: 99%
“…In Portugal, mortality was 14.7% (95% CI: 1.9, 17.5) higher comparing extremely hot days (> 99 th percentile of temperature) to other days in areas in the lowest greenness quartile (NDVI <0.23), but only 3.0% (95% CI: 2.0, 4.0) higher in areas in the highest NDVI quartile (>0.48) [55]. In Korea, mortality was 4.1% (95% CI: 2.3, 5.9) higher per 1 Celsius degree increase for days above the 90 percentile of temperature in areas in the lowest NDVI tertile (<0.341) but only 2.2% (−0.5, 5.0) higher in the highest NDVI tertile (>0.542) [54].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban residents are also generally exposed to poorer physical Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/healthplace environments than their rural counterparts (Burkart et al, 2015;Marzluff et al, 2008;Vlahov et al, 2007) high pollution levels, lack of natural greenspace, and frequent temperature extremes. All these influences have well-documented consequences for the health and survival of the populations (Burkart et al, 2015;Hajat et al, 2007;Shumake et al, 2013;Takano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Urban trees and vegetation provide climate regulation services as they reduce the UHI effect through evapotranspiration and shading and can thus help preventing heatrelated morbidity and mortality (Chen et al 2014). Also urban blue spaces can decrease heat levels and mitigate heat-related morbidity (Burkart et al 2015). In this context, green and blue spaces may therefore be considered as examples of NBS.…”
Section: The Potential Of Urban Green Spaces For Ecosystem Service Prmentioning
confidence: 99%